# Y 5 x 2 2 x 1 so d y d x 52 x 2 0 10 x 1

• vincenthardwick
• 100
• 100% (3) 3 out of 3 people found this document helpful

This preview shows page 42 - 45 out of 100 pages.

y= 5(x22x+ 1), sodydx= 5(2x2 + 0) = 10(x1).Alternatively, multiply out the brackets and then differentiateeach term individually.y= 5(x22x+ 1) = 5x210x+ 5, sodydx= 5×2x10×1 + 0 = 10x10.Activity 11Using the sum ruleDifferentiate the following functions.(a)f(x) = 6x22x+ 1(b)f(x) =23x3+ 2x2+x12(c)f(x) = 5x+ 1(d)g(t) =12t+t(e)f(x) = (1 +x2)(1 + 3x)
248
2Finding derivatives of simple functionsEvery polynomial function (with domainR) is differentiable ateveryvalue ofx.To finish this subsection, here’s a proof of the sum rule, usingdifferentiation from first principles. It uses the Lagrange notation form ofthe sum rule, which is repeated below.Sum rule (Lagrange notation)Ifk(x) =f(x) +g(x), wherefandgare functions, thenk(x) =f(x) +g(x),for all values ofxat which bothfandgare differentiable.A proof of the sum ruleSuppose thatfandgare functions, and that the functionkis given byk(x) =f(x) +g(x). Letxdenote any value at which bothfandgaredifferentiable. To findk(x), you have to consider what happens to thedifference quotient forkatx, which isk(x+h)k(x)h(wherehcan be either positive or negative, but not zero), ashgets closerand closer to zero. Sincek(x) =f(x) +g(x), this expression is equal to(f(x+h) +g(x+h))(f(x) +g(x))h,that is,f(x+h) +g(x+h)f(x)g(x)h,which is equal tof(x+h)f(x)h+g(x+h)g(x)h.The expression in the first pair of large brackets is the difference quotientforfatx, and the expression in the second pair of large brackets is thedifference quotient forgatx. So ashgets closer and closer to zero, thevalues of these two expressions get closer and closer tof(x) andg(x),respectively. Hence the whole expression gets closer and closer tof(x) +g(x). Sok(x) =f(x) +g(x),which is the sum rule.249
Unit 6Differentiation3 Rates of changeYou saw in Unit 2 that the gradient of a straight-line graph is the rate ofxy2¡22(a)xy2¡22(b)Figure 29The lines(a)y= 2x2(b)y=3x+ 1change of the variable on the vertical axis with respect to the variable onthe horizontal axis. For example, if the relationship between the variablesxandy

Upload your study docs or become a

Course Hero member to access this document

Upload your study docs or become a

Course Hero member to access this document

End of preview. Want to read all 100 pages?

Upload your study docs or become a

Course Hero member to access this document

Term
Summer
Professor
NoProfessor
Tags
Gottfried Leibniz, Gottfried Wilhelm
• • • 